Sistem Informasi Manajemen Layanan Pada PDAM Tirta Batanghari - Wibowo Putra, Niko; Mulyono, Herry (LPPM Universitas Dinamika Bangsa, 2023)
Customer satisfaction with PDAM Tirta Batanghari services is related to the level of service quality that can be measured by looking at complaints and feedback from the community. The use of IT can help improve the quality of service at PDAM Tirta Batanghari and is seen as a strategic asset that also determines PDAM Tirta Batanghari's business strategy. This research was carried out with the aim to design itsm information system at PDAM Tirta Batanghari. The method of data collection used is the method of observation and interview, then the data and information obtained are analyzed which results in an analysis of the condition of the system that is running. The system is designed in the form of a protitipe whose design follows each stage of the ITIL process version 4 of the service management area, namely: incident management, service request management, problem management. The results of this study are in the form of a design of ITSM information system at PDAM Tirta Batanghari designed based on itil framework version 4 of service management area.